Phenomenology of domestic violence as a socially deviant phenomenon in Serbia - Andrić, Sanela D; Milašinović, Srđan (Napredak, 2021)
The authors of this paper discusses the phenomenon of domestic violence, which has deep roots, and can be traced from the age of the patriarchate to modern society. The authors explored different types of domestic violence and measures of legal protection against violence. The paper concludes with an all-important sociological approach to the study of this phenomenon. Domestic violence is an individual, group, social / national and global problem, and it is necessary to deal with it, explain it and offer solutions. In contemporary society, which must be synonymous with human rights and freedoms, no form of violence has a place.